Correspondance du contenu sur le site Tv5monde avec les objectifs d’apprentissage de la compréhension orale elémentaire - Annisa Firdayanti; Tri Eko Agustiningrum (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
The learning materials include video transcripts, titles, themes, practical exercises, evaluation indicators, and language levels from the TV5Monde website, adapted to the CPMK in the RPS for the second semester. The use of TV5Monde in the classroom could enhance listening skills, but it has not yet been implemented because the audio and video materials from textbooks are preferred due to their accessibility. This study employs a qualitative approach. It evaluates the relevance of TV5Monde to the learning objectives for oral comprehension skills in the second semester. The results of the relevance analysis between the CPMK learning objectives in the RPS and the TV5Monde website show that out of the 12 videos analysed, 10 were relevant and 2 were not. This positions TV5Monde as an alternative standard for CPMK materials in the RPS for Elementary Oral Comprehension for second-semester students.